Cultural Preservation Strategy Through Tourism : A Case Study of the Surakarta Palace - Dewi Amelia Lestari; Ersyafaat Huda; Johny Subarkah; Arie Restama (An International Journal Tourism and Community Review, 2025)
This research explores cultural preservation strategies through the development of the tourism sector, using the Surakarta Palace as a case study. The Surakarta Palace, a cultural heritage site in Central Java with significant historical and cultural value, plays a vital role in preserving Javanese traditions while contributing to regional tourism growth. This study adopts a descriptive qualitative method with data collected through observation, interviews, and documentation. The findings reveal that the Surakarta Palace actively preserves culture through various initiatives such as organizing traditional ceremonies, staging classical Javanese art performances (like gamelan and wayang), and managing museums that house historical artifacts and royal collections. These strategies serve not only to maintain cultural continuity but also to increase the attractiveness of the palace as a cultural tourism destination. Despite these efforts, several challenges remain. These include limited financial resources, minimal use of digital media for promotion, and the lack of public awareness—especially among younger generations—regarding the importance of cultural heritage. To address these challenges, the study emphasizes the need for integrated collaboration between the government, the Surakarta Palace institution, and the surrounding community. Strengthening digital-based promotional strategies and educational outreach is also considered essential to increase public engagement and sustainable tourism impact. In conclusion, the Surakarta Palace serves as a strategic model for cultural preservation within the tourism framework. By improving stakeholder cooperation and adapting to technological advances, cultural heritage can be preserved effectively while supporting local economic development through tourism. Therefore, cultural preservation and tourism development should be positioned as complementary efforts, where the sustainability of both depends on strategic planning, inclusive participation, and adaptive innovation in facing the dynamic demands of modern tourism.